Fertilizer Management For Wheat Crop In The Himalayan Piedmont Soil (Bangladesh Journal of Agricultural Research, 2013)
An experiment was conducted at the farmers fields in the Himalayan Piedmont soil to evaluate the soil test based (STB) fertilizer dose on wheat crop practicing in the rice wheat cropping sequence during the Rabi season 2002-2003. Three fertilizer treatments: (i) no fertilizer (control), (ii) local farmers fertilizer management practice (FP) and (iii) soil test based fertilizer dose (STB) were tested in 10 farmers fields. The soils of the test fields were acidic and light textured. Results showed that the control plot produced a mean yield of 1.54 t/ha, which increased to 3.96 t/ha with FP and 4.98 t/ha with STB fertilizer dose. The STB fertilizer dose also increased the nitrogen, P, K and S uptake by wheat. Wheat yield showed a strong linear relationship with N, P, K, and S uptake. Partial factor productivity (PFP) of fertilizer (sum of N, P, K and S) was 25.2 kg/kg in FP and that in STB was 24.6 kg/kg. Slightly lower PFP in STB than that of FP may be attributed to the higher dose of N and K in the former. However, the significant yield increase in STB compared with FP encouraged farmers to practice STB fertilizer application for wheat cultivation. Bangladesh J. Agril. Res. 38(2): 241-246, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15887